The Challenges of Immigrant Policy Formation in Trinidad and Tobago: A Civil Society Perspective - Shelly Ann Tirbanie; Michał Pawiński (Cosmopolitan Civil Societies: An Interdisciplinary Journal)
In 2019, the government of Trinidad and Tobago (T&T) embarked on a Venezuelan Registration Exercise with over 16,000 Venezuelan nationals registered. The migratory flows such as the present experience have highlighted the weaknesses in the existing national policy framework of T&T. The inclusion of Civil Society Organizations (CSOs) in the process of policy formation has been limited, while communication with governmental stakeholders to solve the challenges has been underwhelming. The present study conducted interviews with 12 CSOs in T&T with the objective of identifying the challenges they face in forming and implementing migrant policy, their experiences with political stakeholders, and their expectations of future collaboration. The research findings propose the need for the Civil Society Network in T&T and the Caribbean region to address the escalating migratory crisis.